Respiratory immunohistochemical study in rats exposed to cigarette smoke and alcohol - Magnani, Karla Luciana [UNESP]; Cataneo, Daniele Cristina [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Hasimoto, Erica Nishida [UNESP]; Evaristo, Thaiane Cristine [UNESP]; Cataneo, Antônio José Maria [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2015)
To investigate the effects of exposure to cigarette and alcohol on immunohistochemical disorders caused by these attacks to respiratory system of rats. METHODS: Sixty male Wistar rats in four groups: control, cigarette smoke, alcohol and cigarette smoke + alcohol during 260 days. Immunohistochemistry was performed by researching survivin and protein P53 expressions and apoptotic index in parenchymal lung and trachea using TUNEL technique. RESULTS: There was body growth impairment in all experimental groups. Both smoker groups animals had higher trachea survivin expression and bronchial higher apoptotic index. The trachea apoptotic index was also higher in the cigarette smoke group as well as in the alveoli in the cigarette smoke + alcohol group. The three experimental groups showed negative immunoexpression for P53. CONCLUSIONS: this model resulted in immunohistochemical changes caused mainly by exposure to cigarette smoke. There was a synergistic action between alcohol and tobacco in the growth impairment in animals as well as in the cellular apoptotic index. The positive immunoexpression for tracheal survivin in animals from both groups exposed to tobacco smoke and associated with a negative P53 immunoexpression suggests that despite the aggression, carcinogenesis has not happened yet. In addition, the bronchial higher apoptotic index in smokers may be responsible for emphysema.
Keywords: Smoking; Alcoholism; Emphysema; Apoptosis; Rats